2022
DOI: 10.1021/acsami.2c13420
|View full text |Cite
|
Sign up to set email alerts
|

All-Aqueous Microfluidics Fabrication of Multifunctional Bioactive Microcapsules Promotes Wound Healing

Abstract: Wound healing involves multiple stages of body responses, including hemostasis, inflammation, cell proliferation, and tissue remodeling. New material design satisfying all demands throughout different stages of wound healing is cherished but rarely discussed. Here we introduce all-aqueous multiphase microfluidics as a novel strategy to fabricate self-assembled, multifunctional alkylated chitosan/alginate microcapsules (SAAMs) as novel therapeutic materials for rapid blood coagulation and wound healing. SAAMs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 59 publications
(95 reference statements)
0
7
0
Order By: Relevance
“…The fast gelation has further been proved quantitatively using a rheometer, in which the storage modulus ( G ′) of (PEI/PDDA)/(PAA/PSS)/ACS self-gelling powders intersects with the loss modulus ( G ″) at 3 s upon adding phosphate-buffered saline (PBS) buffer (Figure G). A higher storage modulus ( G ′) than the loss modulus ( G ″) indicates the successful transformation from powders to hydrogels. , The gelation time of other similar hydrogel powders has been reported to be around 2 s , The prolonged gelation time of our self-gelling powders is due to the incorporation of ACS, whose hydrophobicity would affect the interaction between its polymeric chains and the surrounding liquid.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…The fast gelation has further been proved quantitatively using a rheometer, in which the storage modulus ( G ′) of (PEI/PDDA)/(PAA/PSS)/ACS self-gelling powders intersects with the loss modulus ( G ″) at 3 s upon adding phosphate-buffered saline (PBS) buffer (Figure G). A higher storage modulus ( G ′) than the loss modulus ( G ″) indicates the successful transformation from powders to hydrogels. , The gelation time of other similar hydrogel powders has been reported to be around 2 s , The prolonged gelation time of our self-gelling powders is due to the incorporation of ACS, whose hydrophobicity would affect the interaction between its polymeric chains and the surrounding liquid.…”
Section: Resultsmentioning
confidence: 78%
“…Severe trauma wounds can cause devastating consequences, including fatal blood loss, shock, infection, and life-threatening injuries . Achieving rapid hemostasis hence becomes vital during wound management. , Wound caring in clinical research has attracted a surge of interest from the science community, with a primary concern on developing ideal wound dressing, which should hold the following requirements: rapid blood cell aggregation to halt bleeding (hemostasis), strong adhesion on the bleeding wounds without the need of compression, sufficient mechanical properties to provide a physical barrier on the wounds to maintain blood pressure, good hemocompatibility and biocompatibility, and continuous protection against bacterial infection. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of wound healing can be divided into three stages, which include inflammatory, proliferative, and remodeling. In the early and entire phase of inflammation, the accelerated recruitment of cytokines and immune cells is very important. It has been shown that endogenous electric fields can promote the migration of macrophages, lymphocytes, and neutrophils to skin wound sites and ultimately promote wound healing .…”
Section: Applying Tengs-based Es For Promoting Wound Healingmentioning
confidence: 99%
“…[14][15][16] From the perspective of the treatment strategy, hemostasis and remodeling could be achieved well passively by the body itself: the aggregation of platelets and the formation of fibrin clots could stop bleeding effectively, while the generated collagen in the proliferation stage would arrange and cross-link to achieve structural and mechanical remodeling. [17][18][19] Different from hemostasis and remodeling, active drug intervention (such as antibiotics and growth factors) is usually additionally required in the inflammation and proliferation stages to help the human body kill foreign organisms and promote the growth of new tissue. [20][21][22][23] Therefore, it is highly desired to construct a multidrug loaded wound dressing with a controlled gradient drug release kinetics to meet the diverse requirements of the drug type and release time point at the inflammation and proliferation stages.…”
Section: Introductionmentioning
confidence: 99%